God's relational presence : the cohesive center of biblical theology - Duvall, J. Scott; Hays, J. Daniel, 1953- (Michigan Baker Academic, 2019)
"Two leading biblical scholars explain that relational presence is central to the grand narrative of the Bible, showing that the thread running from Genesis to Revelation is God's desire to be with his people"--
Includes bibliographical references and indexes.
Keywords: Bible -- Theology; Presence of God; God -- Biblical teaching